Application of geomatics in la Rioja heritage. Cathedral church San Nicolás de Bari - Ariaudo, Esteban Adrián (2024)
The research presented here was carried out within the framework of the cooperation agreement between the National University of La Rioja (Argentina) and the Universitá degli Studi di Firenze (Italy), which was based on the opportunity to carry out, for the first time , a complete metric-three-dimensional survey of the architectural structure of the Cathedral of San Nicolás de Bari, thanks to new scanning technologies. This study has been carried out in order to contribute an exemplary action of synergy between various disciplinary approaches and methods for the creation of an essential database for the planning and improvement of a comprehensive survey and restoration project. The great development of technology applied to the heritage sector has led to the automation of survey systems, offering new questions about the methods of managing data and exploring the most efficient and complete forms of representation of spatial objects and space. human The result of the present investigation constitutes the first important document of this nature, produced by the relationship of academic exchange of knowledge and experiences.